Respuesta :

Let us represent the unknown number using the variable x.

The difference of the number and 4 is represented by x - 4.

Twice their difference would be 2(x - 4).

The sum of the same number and 3 is represented by x + 3.

Three times their sum is then represented by 3(x + 3).

The complete equation is then:

[tex]2(x-4)=3(x+3)[/tex]

To solve for the unknown number, let's simplify using the properties of equality.

[tex]\begin{gathered} 2(x-4)=3(x+3) \\ \\ 2x-8=3x+9 \\ \\ 2x-3x=9+8 \\ \\ -x=17 \\ \\ x=-17 \end{gathered}[/tex]

The missing number is -17.

ACCESS MORE
EDU ACCESS
Universidad de Mexico